Contests: Theory and applications - Bevia, Carmen; Corchon, Luis (New York Cambridge University Press, 2024)
Contest theory is an important part of game theory used to analyse different types of contests and conflicts. Traditional microeconomic models focus on situations where property rights are well defined, and agents voluntarily trade rights over goods or produce rights for new goods. However, much less focus has been given to other situations where agents do not trade property rights, but rather fight over them. Contests: Theory and Applications presents a state-of-the art discussion of the economics of contests from the perspective of both core theory and applications.